Numerical modelling on the performance of submerged breakwater using the SPH-based DualSPHysics model - Ramli, Muhammad Zahir; Hikmatullah Sahib, Siti Ayishah Thaminah; Ab Razak, Mohd. Shahrizal; Miskon, Mohd Fuad; Yunus, Kamaruzzaman; Ariffin, Effi Helmy; Jeofry, Muhammad Hafeez (2022)
Implementation of coastal structures are known to mitigate issues of coastal erosion and impacts of sea waves during storm events on coastal areas. Among the various coastal structures implemented in Malaysia, the submerged breakwater called as WABCORE is being studied. This structure was originally designed by the National Hydraulic Research Institute of Malaysia and has been implemented at the shores of Pulau Tinggi, Johor, Malaysia. The objective of this study is to identify the wave transmission coefficient of the improved WABCORE structure under a variety of wave conditions. The effect of wave steepness (Hi/L) parameter on the wave transmission coefficient would also be highlighted. The study also considers the arrangement of the WABCORE structures, whereby the structures are stacked in a 4:3:2 (broad) and 3:2:1 (narrow) manner. This study implements the use of an open-source code known as DualSPHysics to simulate the various conditions. The results signify that the WABCORE structure is capable of dissipating waves despite its various condition.